The promise of stem cells in amyotrophic lateral sclerosis: a review of clinical trials - Muhammad Usman Khalid; Taleaa Masroor (Journal of the Pakistan Medical Association, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative condition with high cost of care, poor treatment outcomes, and a significant decrease in quality of life, eventually culminating in high mortality rates. Stem cells present an attractive alternative to conventional therapies as they can regenerate tissue and introduce growth factors to slow down the progression of disease. We conducted a comprehensive review of literature available in the MEDLINE (PUBMED), Scopus, and Cochrane Library databases, of current usage of stem cells and stem cell-based biomaterials for ALS treatment. Clinical trials, less than 10 years old, on human subjects were included in the study. Overall, stem cells, whether mesenchymal, non-lineage, or neural stem cells all seem safe for use in therapy for ALS. However, due to the chronic nature of the disease the efficacy of the treatment is not proven and warrants further investigation. Keywords: Amyotrophic Lateral Sclerosis. Biocompatible Materials, Neural, Stem Cells